Concordance and predictors of concordance of children's dietary intake as reported via ecological momentary assessment and 24 h recall. Issue 6 (21st January 2018) - O'Connor, Sydney G; Ke, Wangjing; Dzubur, Eldin; Schembre, Susan; Dunton, Genevieve F
Abstract: Objective: To provide preliminary evidence in support of using ecological momentary assessment (EMA), a real-time data capture method involving repeated assessments, to measure dietary intake in children by examining the concordance of children's dietary reports through EMA and 24 h recall. Design: Children completed eight days of EMA surveys, reporting on recent dietary intake of four pre-specified food categories ('Fruits or Vegetables', 'Chips or Fries', 'Pastries or Sweets', 'Soda or Energy Drinks'), and completed two 24 h recalls during the same period. Concordance of children's reports of intake during matched two-hour time windows from EMA and 24 h dietary recall was assessed using cross-tabulation. Multilevel logistic regression examined potential person-level (i.e. sex, age, ethnicity and BMI category) predictors of concordance. Setting: Children in Los Angeles County, USA, enrolled in the Mothers' and Their Children's Health (MATCH) study. Subjects: One hundred and forty-four 144 children (53 % female; mean age 9·6 (sd 0·9) years; 34·0 % overweight/obese). Results: Two-hour concordance varied by food category, ranging from 64·9 % for 'Fruits/Vegetables' to 89·9 % for 'Soda/Energy Drinks'. In multilevel models, overweight/obese ( v . lean) was associated with greater odds (OR; 95 % CI) of concordant reporting for 'Soda/Energy Drinks' (2·01; 1·06, 4·04) and 'Pastries/Sweets' (1·61; 1·03, 2·52). Odds of concordant reporting were higher for Hispanic ( v . non-Hispanic) children for 'Pastries/Sweets' (1·55; 1·02, 2·36) and for girls ( v . boys) for 'Fruits/Vegetables' (1·36; 1·01, 1·83). Conclusions: Concordance differed by food category as well as by person-level characteristics. Future research should continue to explore use of EMA to facilitate dietary assessment in children.